Pengakuan Pendapatan dan Beban Perusahaan Jasa Konstruksi Pada PT. Jaya Abadi Sriwijaya - Sulbahri, Rifani Akbar; Putri, Yuni Adinda; Rachmawati, Yuni (Universitas katolik Musi Charitas, 2021)
he more intensive the development, the more mushrooming of construction service companies in Indonesia. The high competition is also a challenge for this company to be able to survive and even become superior in its class. The performance of construction companies can certainly be seen in the financial statements that can be compared per period. Problems arise when the construction company's expenses have occurred but the income has not been obtained, while in that period it is necessary to present financial statements. is implemented. In construction companies, there is a specific point in determining the timing of revenue, namely the point at which revenue must be recognized and reported. In general, revenue is recognized when the work is completed. However, according to financial accounting standards, it is possible for construction companies to recognize revenue during the course of production in accordance with the stage of contract completion. PSAK No. 34 of 2010 concerning accounting for construction contracts describes the accounting treatment of income and expenses related to construction contracts, the date when the activity is started and the date when the activity is completed usually falls on a different date. company. Improper performance appraisal will make management decisions that are not right as well. Therefore, socialization in the form of assistance in recognizing the income and expenses of construction companies needs to be carried out at PT Jaya Abadi Sriiwijaya